Effect of Information Disclosure on Corporate Performance: Evidence from Companies in Pharmaceuticals and Chemicals Industry Sectors of Dhaka Stock Exchange (Dhaka University Journal of Business Studies, 2023)
In this study we examined if level of corporate disclosure (mandatory, voluntary, and combined) has any impact on firms’ performance (measured in terms of ROA, ROE and stock return) in case of Bangladeshi listed firms. The data from 15 listed companies of pharmaceuticals and chemicals sectors is used covering study period of 10 years (2009-2018). The dataset is analysed using both descriptive statistics and random effect model following the models used by similar studies in other countries. Beside indices of disclosure, some other control variables like sales growth, age of firm, size of firm, leverage ratio, total asset turnover and industrial category of the firm (pharmaceuticals or chemicals) are used in three different models as proxy for returns. The results indicate that firms with higher level of mandatory or combine disclosure have higher ROE or ROA.Journal of Business Studies, Vol. XLII, No. 2, August 2021 Page 1-24